Prototype Of an IoT-Based Generator Fuel Level Monitoring and Control System at The Electricity Unit of PERUM LPPNPI JATSC Branch - Ayu Dwi Andini, Niken; Irfansyah, Ade; Artha Wirawan, Willy (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
Generators are a critical backup power source for maintaining operational continuity in various sectors. However, manually monitoring the fuel level of a generator results in a lack of efficiency and can lead to delays in refueling, even leading to sudden fuel outages. This situation can affect the availability of backup power when needed. Therefore, this study aims to design and implement an Internet of Things (IoT)-based fuel level monitoring system that can monitor directly, provide automatic notifications when the fuel level is low, and control the fuel filling pump automatically. The development method chosen is the Waterfall model, which includes the stages of analysis, design, implementation, and system testing. The hardware used includes a NodeMCU ESP32 as a microcontroller, a HY-SRF05 ultrasonic sensor to detect fuel level, a relay for DC pump control, and a buzzer as an alarm signal. All data is sent directly to the Blynk application as a monitoring medium. Test results show that the system can read fuel level with an error rate between 0.01% and 3%, while the conversion into liters shows a maximum deviation of 2.6%. This system also successfully controls pumps and alarms automatically according to existing logic. Thus, this system can improve efficiency and accuracy in generator fuel monitoring.